A Cat Nap - Clay, Shannon (USA)
Pam. I am Pam. A cat. A sad, sad cat. I can pat a sad cat. I can go to Nan. A tag! A cat tag! My cat! My cat, Tam! My cat can nap! A cat nap!...
Keywords: Animal Story; Juvenile Fiction